Analisis Penilaian Pelayanan Puskesmas Terhadap Pemberian Vaksin COVID-19 dengan Metode K-Means Clustering - Sriani, Sriani; Suhardi, Suhardi; Damanik, Masliana (Jurnal Ilmiah Matrik, 2024)
The Public Health Center is responsible for implementing health policies to achieve health development goals in its area, supporting the realization of a healthy sub-district. One example is the Negeri Lama Public Health Center in Bilah Hilir Sub-district, Labuhanbatu Regency, which serves eight villages with a total population of 36,370 in 2021. The quality of services provided influences patient perceptions, making it essential to continuously improve service quality. This study categorizes the assessment of COVID-19 vaccination services at Negeri Lama Public Health Center using the K-Means Clustering method. This method classifies data into three categories: Very Good Service, Good Service, and Poor Service. The study results show that the Very Good Service category includes six variables with a centroid of 0.519667, the Good Service category includes two variables with a centroid of 0.4605, and the Poor Service category includes two variables with a centroid of 0.3795. This method is considered effective in managing large data accurately